2010
DOI: 10.1143/jjap.49.121301
|View full text |Cite
|
Sign up to set email alerts
|

Micro Defect Size in Si Single Crystal Grown by Czochralski Method

Abstract: Single crystals for 300 mm wafer are grown by horizontal magnetic Czochralski method. 300 mm wafers are made from the vertical samples cut from crystal along ingot axial direction. Micro defects in various defect regions are investigated with various measurement methods. In order to investigate the size of the defects, the locations of defects are identified, the wafers with the defects are cut in cross-sectional direction, and the sizes of the defects are measured by transmission electron microscopy (TEM). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…3. Results and discussion Figure 2 shows the OM images of Cu precipitates in the specimens S15 taken along the radial direction of the 300 mm CZ silicon wafer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Results and discussion Figure 2 shows the OM images of Cu precipitates in the specimens S15 taken along the radial direction of the 300 mm CZ silicon wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the grown-in oxygen precipitates are too small to be observed by the common light-scattering and etching techniques. Even for transmission electron microscopy (TEM), it is generally appropriate for revealing the grown-in defects in size larger than 20 nm [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both local and widespread nonuniformity often exists in the grown crystal. 9,10 To address this very important problem, we have proposed rapid thermal oxidation (RTO) at ultrahigh temperature (ultrahigh-temperature RTO).11 Our results obviously demonstrated that the oxygen precipitates generated during the crystal growth were dissipated entirely, and dense oxygen precipitate nuclei were formed uniformly in the radial direction during RTO at temperatures over 1350• C. We believed that the newly formed oxygen precipitates in the wafers that had been subjected to ultrahigh-temperature RTO were closely related to preserved vacancies. In particular, each oxygen precipitate nucleus is thought to consist of an oxygen-vacancy complex (for example, O 2 V).…”
mentioning
confidence: 99%
“…Thus, both local and widespread nonuniformity often exists in the grown crystal. 9,10 To address this very important problem, we have proposed rapid thermal oxidation (RTO) at ultrahigh temperature (ultrahigh-temperature RTO).…”
mentioning
confidence: 99%
See 1 more Smart Citation